Eccentric strengthening vs. conventional therapy in sub-acute stroke survivors: a randomized controlled trial - Belghith, Kalthoum; Zidi, Mustapha; Vincent, Lhéo; Fedele, Jean-Michel; Bou-Serhal, Rayan; Maktouf, Wael (Frontiers in Neurology, 2025)
Spastic paresis, a common consequence of stroke, involves both neurological and muscular changes, leading to decreased muscle strength and increased passive muscle stiffness. Current rehabilitation approaches focus on spasticity reduction but often overlook spastic myopathy, contributing to limited motor improvement. Eccentric Training (ET) has emerged as a potential solution due to its ability to enhance muscle strength and extensibility. However, its effectiveness in addressing post-stroke neuromuscular impairments remains underexplored. This study aims to investigate the impact of ET on gait speed in sub-acute stroke patients compared to conventional therapy. Additionally, we aim to explore the effects of ET on the mechanical properties, structural characteristics, and neuromuscular parameters of the plantar flexors. A randomized controlled trial will be conducted, adhering to CONSORT guidelines, with participants assigned to either a Conventional Therapy Group or an Eccentric Training Group. Assessments will be conducted at baseline, and after ET intervention, encompassing clinical, biomechanical, and functional evaluations. This study seeks to provide empirical evidence on the efficacy of ET in improving motor outcomes and addressing spastic myopathy in sub-acute stroke patients, thereby informing more effective rehabilitation strategies.